A TRANSGENIC APPROACH TO STUDY THE EFFECT OF CARDIAC FIBROBLAST-SPECIFIC ABLATION OF IL-1 SIGNALLING ON MYOCARDIAL REMODELLING. (21st November 2014) - Hemmings, KE; Bageghni, SA; Porter, KE; Drinkhill, MJ; Ainscough, JFX; Turner, NA
Abstract : Introduction: Cardiac fibroblasts (CF) play a critical role in the repair of the heart following MI, but aberrant remodelling can lead to fibrosis and heart failure. We have previously demonstrated that interleukin-1 (IL-1), a key proinflammatory cytokine released following MI, is a potent modulator of CF function. The aim of this study was to develop a mouse model with fibroblast-specific ablation of IL-1 signalling through deletion of Myd88. Methods: We generated a mouse line with tamoxifen-inducible Cre-recombinase under control of the fibroblast-specific Col1a2 promoter, and loxP sites flanking exon 3 of the Myd88 gene, an essential component of the IL-1 receptor signalling complex. Mice were administered tamoxifen (75–100 mg/kg; i.p; 5 days) to induce Myd88 deletion. DNA was obtained from ear notches and RNA from cultured CF. Myd88 DNA deletion efficiency and mRNA expression levels were determined by real-time RT-PCR. All data are expressed as mean±SEM %GAPDH. Results: Tamoxifen induced a 32% reduction in Myd88 DNA (Cre- 0.172±0.017 (n=7) vs. Cre+ 0.117±0.015 (n=9); P=0.049) and a 63% reduction in CF Myd88 mRNA expression (Cre- 1.64±0.27 (n=4) vs. Cre+ 0.60±0.25 (n=4); P=0.023). Expression of DDR2 mRNA, a fibroblast marker, was unaffected (Cre- 0.91±0.06 vs. Cre+ 0.77±0.10; P=0.279) indicating the specificity of Myd88 deletion. Increasing tamoxifen dose (100 mg/kg) did not enhance deletion efficiency. Conclusions: We have successfully reduced expression of Myd88 in CF from tamoxifen-treated Cre+ animals. To obtain greater deletion efficiency we propose using a PGK-Cre line to globally delete one Myd88 allele in the germline prior to tamoxifen-induced ablation in CF.